Emerging drugs for neuroblastoma. (June 2013) - Castel, Victoria; Segura, Vanessa; Berlanga, Pablo
Abstract : Introduction: Neuroblastoma accounts for 8 – 10% of pediatric cancers and is responsible for 15% of childhood cancer deaths. Despite multimodality treatment, the overall survival (OS) and event-free survival (EFS) in high-risk patients remain suboptimal. More than half of children diagnosed with high-risk neuroblastoma either do not respond to conventional therapies or relapse after treatment. Areas covered: This review discusses about the unmet medical needs for new therapeutic options against high-risk neuroblastoma. New drugs and therapeutic strategies that are under development in clinical trials, which are currently recruiting patients. Expert opinion: There is a need to improve the response rate of induction chemotherapy, which is not effective in a third of patients and also the other components of the current treatment, little efficacious in avoiding the relapses. Few drugs have been introduced as upfront therapy in the last years. Topotecan, irinotecan and temozolomide are expected to improve the response in high-risk neuroblastoma, but their impact on OS and EFS is unknown. Anti-GD2 antibodies combined with other immunomodulators (IL-2, GM-CSF) are an important advance in the treatment of these children. Nevertheless, the hope is put in the new drugs directed to molecular targets of neuroblastoma. Anti-angiogenic drugs, ALK antagonist and PI3K/Akt/mTOR inhibitors are among the most promising.